A compressive study between jump vs land phase by some biomechanics and EMG variables during spike in volleyball - A. Hassan, Mohammad; A. ismeel, Safaa; Salih Neamah, Nagham (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to investigate the amount of some biomechanical variables (fly angle/land, horizontal displacement HD, angle of knee and hip, impulse and braking impulse) and electromyography (area under curve AUC, time before peak TBP, and time after peak TAP) for targeted muscle groups in the leg (LAT. GASTRO, TIB.ANT., RECTUS FEM., BICEPS FEM.). The subjects (10 M, age 20–24 years) who participated in the Iraqi league during spike in volleyball. The technical that depended to record muscle activity was Myotrace 400 from Noraxon Company, and to determine biomechanical variables we used Techno DYNAFOOT©. DYNAFOOT2 software is compatible with computers, laptops, and tactile tablets under the Windows operating system and equipped with a Bluetooth connection. Also, we used a Casio digital high-speed camera (320 f/s) to investigate joint angles, which were analyzed by Kinovea v.8.15 software. The result comes to show us there is a significant difference between two types of EMG variables, so in some biomechanics.